Enhanced energy storage and discharge-charge performance by changing glass phase content in potassium sodium niobate glass-ceramics. Issue 8 (1st June 2020) - Du, Xinyi; Pu, Yongping; Peng, Xin; Li, Run; Zhang, Qianwen; Chen, Min; Liu, Gang
Abstract: (1- x ) (K2 O–Na2 O–2Nb2 O5 )- x (2BaO–Nb2 O5 –2SiO2 ) glass-ceramics with x = 0.10, 0.15, 0.20, 0.25 have been successfully prepared by traditional melting method. XRD and microstructure analysis demonstrate that all glass-ceramics are crystallized into uniform Na0.9 K0.1 NbO3 and K2 (NbO)2 (Si4 O12 ) ferroelectric crystalline phase. Increasing x promotes the formation of Ba2 NaNb5 O15 phase with a tungsten bronze structure. Raman and complex impedance data confirmed that Ba 2+ is introduced to repair the disruption of the glass network and make carrier migration difficult when x = 0.15. Thus, the x = 0.15 glass-ceramic sample possesses a maximum calculated energy storage density of 2.32 J/cm 3 under 820 kV/cm because of a high degree of polymerization (DOP) glass network structure. Moreover, the pulsed discharge-charge tests are carried out to evaluate actual energy storage performance.